Experimental Study on Sweep Characteristics of Gas Gravity Drainage in the Interlayer Oil Reservoir - Yu, Hongwei; Wang, Lu; Zhou, Daiyu; Wang, Fuyong; Li, Shi; Li, Jun; Chen, Xinglong; Cao, An; Han, Haishui (Frontiers in Energy Research, 2021)
Stable gas gravity drainage is considered as an effective method to enhance oil recovery, especially suitable for deep buried, large dip angle, and thick oil reservoirs. The influence of reservoir heterogeneity on controlling the gas-oil interface and sweep characteristics of injected gas is particularly important to design reservoir development schemes. In this study, according to the interlayer characteristics of Donghe carboniferous oil reservoirs in Tarim Basin, NW China, 2D visual physical models are established, in which the matrix permeability is 68.1 mD and average pore throat radius is 60 nm. Then, hydrocarbon gas gravity drainage simulation experiments were carried out systematically, as well a high-speed camera was used to record the process of gas-oil flow and interface movement. In this experiment, the miscible zone of crude oil and hydrocarbon gas is observed for the first time. The interlayer has an obvious shielding influence, which can destroy the stability of the gas-oil interface and miscible zone, change the movement direction of the gas-oil interface, and reduce the final oil recovery after gravity drainage. The remaining oil mainly distributes near the interlayers. The higher displacement pressure leads to more stability of the gas-oil displacement front and later gas breakthrough, which leads to higher oil recovery. The lower gas injection rate contributes to slower front velocity and wider miscible zone, which could delay gas breakthrough. For the immiscible gas gravity drainage, there is a critical gas injection rate, with which the oil recovery factor is the highest.